Workplace Challenges in the Local Government Unit of Polangui, Albay, Philippines: An Analysis of Communication Skills and Human Relations - Coronado, Princess Zarah; Reyes, Ma. Josefa Sario; Britanico, KC Baydal (Jurnal Genesis Indonesia, 2025)
This study aimed to determine the workplace challenges faced by employees of the Local Government Units (LGUs) of Polangui, Albay, Philippines, specifically in the areas of communication skills and human relations. The study utilized a descriptive-quantitative research design and employed a chi-square test to assess the association between respondents' demographic profiles and their communication and interpersonal skills. Results indicated that most profile variables, such as age, sex, employment status, management level, office assignment, and seminar attendance, had no significant influence on communication skills or human relations. However, highest educational attainment and eligibility status showed a statistically significant relationship with both communication skills (p < 0.05) and human relations (p < 0.05), suggesting that higher education and certifications positively impact workplace competencies. These findings support previous literature indicating that formal education and professional qualifications play a crucial role in developing effective communication and interpersonal interactions in professional settings. The results also imply the need for continued capacity building and targeted training programs for LGU personnel to enhance workplace effectiveness.